2000
DOI: 10.1002/1096-9861(20000807)423:4<646::aid-cne9>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor applied to the optic nerve after injury increases long-term cell survival in the frog retina

Abstract: The neuroprotective effects of basic fibroblast growth factor (bFGF) on the long-term survival of axotomized retinal ganglion cells (RGCs) were studied in the frog Rana pipiens. Cell loss was quantified in different regions of the ganglion cell layer using Nissl staining and tetramethylrhodamine dextran amine backfilling. All regions of the retina showed a significant decrease (32-66%) in RGC numbers between 4 and 16 weeks after axotomy. Some cells showed morphological and biochemical signs of apoptosis. A sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 59 publications
4
47
0
Order By: Relevance
“…Several animal studies have indicated that the application of bFGF could possiblely promote the survival of RGCs, and stimulates regrowth of the axons within the injured optic nerve [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Several animal studies have indicated that the application of bFGF could possiblely promote the survival of RGCs, and stimulates regrowth of the axons within the injured optic nerve [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Application of these factors, and the activation of their intracellular pathways, promotes the survival and axonal regeneration of axotomized RGCs (Blanco et al, 2008, 2000; Ríos-Muñoz et al, 2005; Soto et al, 2006b; Vega-Meléndez et al, 2014). All-trans retinoic acid (ATRA) is an important morphogen that controls the patterning and differentiation of neurons during development, and it has also been identified as a signaling molecule and transcriptional activator that regulates the expression of target genes, including those of growth factors and their receptors (Arrieta et al, 2005; Hernández-Pedro et al, 2008; Katsuki et al, 2009; Kurauchi et al, 2011; Qi et al, 2015; Wang and Halvorsen, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The frog visual system is similar to the mammal's in that many of its RGCs die after axotomy (Blanco et al, 2000), but like that of the fish in that the surviving RGCs are able to regenerate and reconnect with their targets in the optic tectum (Soto et al, 2006a, 2003). Both the survival rate, and regeneration speed, of the frog's RGCs can be augmented by application of growth factors to optic nerve or eyeball, and we have studied the molecular pathways involved (Blanco et al, 2008, 2000; Ríos-Muñoz et al, 2005; Soto et al, 2006b; Vega-Meléndez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic fibroblast growth factor (bFGF) is a member of the FGF family that has been shown to protect neurons against injury and degeneration 5) . bFGF increases long-term cell survival in frog retinal ganglion cells after optic nerve axotomy 6) . In vitro actions of bFGF on mesenchymal and neuroectodermal cells include induction of or increase in proliferation, mitogenesis in glial cells, the support of neuronal survival, the promotion of neurite outgrowth 7,8) , morphological changes, anchorage-independent growth, differentiation, delayed senescence, angiogenesis, neovascularization, tissue differentiation, regulation of tissue specific functions 9) , wound healing 10) , other regenerative processes, abnormal cell differentiation and growth 9) .…”
Section: Introductionmentioning
confidence: 99%